Professionalism versus democracy?: historical and institutional analysis of police oversight mechanisms in three Asian jurisdictions - Ho, Lawrence K. K. (Crime, law and social change, 2022)
Should police be checked by the police or by representatives with public mandates? This article aims to respond to this frequently asked question by comparing two sets of institutional arrangements in police oversight mechanisms under three Asian regimes with different levels of democratization: Hong Kong, Japan, and Taiwan. "Professionalism" and "transcendency" are often prioritized by the Hong Kong authorities as the merits of the internal affairs model, over independent investigation capacity or elected appointees. Paradoxically, its police oversight counterparts under two neighbouring constitutionally democratic Asian jurisdictions still face critiques, given their institutional proximity with the civilian control model prevailing in the Western countries. What kind of institutional setting better oversight the police? We conducted a historical-institutional analysis by making use of publicly accessible documents, examining the evolution, reviewing the missions and format of empowerment, and weighing the strength and key insufficiencies of these three police oversight mechanisms. Our study primarily finds that historical conjunctures and regime values appear decisive in the evolution of these bodies. The police oversight mechanisms in Japan and Taiwan place more emphasis on public representation and legal empowerment to check police power, which provides longer institutional stability than that of Hong Kong, which was credited on personnel capability or transparency of the investigation process. The study also finds that the competence of personnel and the transparency of the investigation process appear not comparable to the importance of the public representation and legal authorization of the oversight agencies in determining public trust towards the oversight mechanism.